(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Swimming is ability of man to keep in place in water or to move on the water surface by horizontal movements of his own locomotion. Swimming performance is determined by various factors. Purpose of this study was to predict 50 m swimming performance on the basis of selected physical variables. A total of 20 swimmers aged 18-30 years, with at least 1 year of swimming experience were chosen. They underwent testing of leg explosive strength, shoulder strength, abdomen strength, shoulder flexibility, trunk-hip flexibility and ankle flexibility and finally the recording of the 50m sprint swimming time in freestyle swimming. Multiple linear regression was used as statistical technique. In results, statistically significant negative correlations (p